THE IMPORTANCE OF HYPERESTROGENEMIA IN ENDOMETRIAL CANCER - Tursunova Nodira Isroilovna; Abdinazarova Iltifot Sodiqjon qizi; Omonova Nilufar Orzuevna (Web of Journals Publishing, 2025)
Hyperestrogenemia plays a significant role in the pathogenesis of endometrial cancer, particularly in type I endometrioid adenocarcinomas. The imbalance between estrogen and progesterone, favoring unopposed estrogen stimulation, leads to endometrial hyperplasia and carcinogenesis. This article examines the biological mechanisms linking estrogen excess to tumor development, evaluates diagnostic and prognostic implications, and highlights preventive and therapeutic strategies targeting hormonal regulation. The study integrates findings from molecular, clinical, and epidemiological research to underline the importance of hormonal balance in endometrial health.
Keywords: Hyperestrogenemia, endometrial cancer, estrogen receptors, progesterone deficiency, hormonal carcinogenesis, endometrial hyperplasia, risk factors, gynecologic oncology